KNi0.93FeII0.07FeIII(PO4)2: a new type of structure for a compound of composition MIMIIMIII(PO4)2. Issue 2 (15th February 2014) - Strutynska, Nataliya Yu.; Zatovsky, Igor V.; Baumer, Vyacheslav N.; Ogorodnyk, Ivan V.; Slobodyanik, Nikolay S.
<x xml:space="preserve">Abstract</x> The solid solution KNi0.93FeII0.07FeIII(PO4)2 {potassium [nickel(II)/iron(II)] iron(III) bis(orthophosphate)} has been prepared by the flux method. The compound shows a new type of structure for a phosphate with the general composition MIMIIMIII(PO4)2. The framework is formed by [(Ni/Fe)O6] polyhedra [Fe site occupancy = 0.069 (14)] linked via shared oxygen vertices forming a cis‐like parallel chain stretching along a and [FeO5] polyhedra (located on alternate sides of the chains) connected via two types of PO4 groups into a three‐dimensional structure. The K atoms are disordered between two sites, denoted K1A and K1B, with occupancies of 0.930 (9) and 0.070 (9), respectively, and reside inside channels along the a axis. Calculations of the Voronoi–Dirichlet polyhedra of the K atoms give a coordination scheme for K1A of [9 + 3] and for K1B of [10 + 2]. The most remarkable feature of the structure is the splitting of the K‐atom site and the population of the K1A and K1B positions due to substitution of Ni by Fe in the (Ni/Fe) position.